Science Teacher Education Considering the Covid-19 Pandemic: The African Account - Badmus, Olalekan Taofeek; Amuda, Afees Akanni; Akanbi, Abdulrasaq Oladimeji; Omosewo, Esther Ore (Jurnal Pendidikan Matematika dan Sains, 2022)
The outbreak of Covid-19 the world over is devastating. The responses to the disruptions experienced had left many nations in doubt of a possible recovery in years to come. Various sectors of human needs were distorted, and the socioeconomic impact cannot be overestimated. The education sector is one of the first sectors to be locked down immediately after the emergence of the pandemic and about the last to be recalled after the first wave of Covid-19. Education institutions are experiencing massive reforms globally amid the Covid-19 outbreak and the effect of the lockdown is enormous. The economic impact of the pandemic is more pronounced than the academic, especially in science and science teacher education. This paper investigated science teacher education considering the Covid-19 pandemic. Specifically, this research explored the African account of Covid-19, the effect of Covid-19 on science teacher education, the rationale for a rethink in science teacher education amidst Covid-19, the limitations to science teacher education post-Covid-19 and the way forward for stakeholders amid/post Covid-19. This article concluded among others that more is required in terms of investment in the education sector to actualize the modern approaches required to cope with the pandemic situations in Africa.